Hypoglycemic and Antioxidative Effects of Chromium, Magnesium, and Cinnamon Fortified Parboiled Rice on Diabetic Rats - Leba, Herlyn; Yulianto, Wisnu Adi; Pujimulyani, Dwiyati (Journal Akademik Universitas Swiss German, 2022)
One of the strategies to manage diabetic blood glucose is through the consumption of foods with a low glycemic index (GI) such as parboiled rice with adequate chromium and magnesium. In diabetes, insulin resistance leads to impaired glucose metabolism and oxidative stress. This oxidative rate can be prevented by adding to the intake of antioxidants from cinnamon. Therefore, this research aimed to determine the effect of chromium, magnesium, and cinnamon fortified parboiled rice on hypoglycemic and antioxidant activities in diabetic rats. The clinical trial treatments on rats with dietary intake were given for 28 days in 6 groups, namely healthy rats with standard feed and diabetic rats with standard feed milled or non-parboiled rice, non-fortified parboiled rice Cr and Mg fortified parboiled rice as well as Cr, Mg, and cinnamon fortified parboiled rice (DRFCP). The analysis carried out included glucose, insulin, malondialdehyde (MDA) levels, and statistical analysis using One-Way Anova. The results showed that in the DRFCP group, glucose and MDA levels decreased significantly (p <0.05) from 258.63 mg/dL to 111.19 mg/dL (57%) and 9.28 ng/mL to 1.96 ng/mL (78.87%), while the insulin levels increased significantly (p <0.05) from 413.97 ug/dL to 540.65 ug/dL (30.60%). This type of feed (DRFCP) can be used as a diet for diabetes because it can reduce blood glucose and malondialdehyde levels.